2009
DOI: 10.1017/s0958344009000032
|View full text |Cite
|
Sign up to set email alerts
|

Mobile blogs in language learning: making the most of informal and situated learning opportunities

Abstract: The application of mobile technologies to learning has the potential to facilitate the active participation of learners in the creation and delivery of content. Mobile technologies can also provide a powerful connection between a variety of formal and informal learning contexts and can help to build a community of learners. However these versatile tools present challenges to educators and learners alike. The paper discusses the pedagogical challenges that result from the introduction of mobile technologies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(84 citation statements)
references
References 17 publications
2
75
0
1
Order By: Relevance
“…Several studies reported a positive relationship between mobile usage and language learning (Horen and Palala, 2011;Baleghizadeh & Oladrostan, 2010;Comas et al, 2009). In addition, smart devices were linked to faster reading and self-regulated style of learning among students (Kondo, 2012).…”
Section: Smart Devices \ Social Media and Students' Attitudes Towardsmentioning
confidence: 99%
“…Several studies reported a positive relationship between mobile usage and language learning (Horen and Palala, 2011;Baleghizadeh & Oladrostan, 2010;Comas et al, 2009). In addition, smart devices were linked to faster reading and self-regulated style of learning among students (Kondo, 2012).…”
Section: Smart Devices \ Social Media and Students' Attitudes Towardsmentioning
confidence: 99%
“…Activities as such, in Herrington and Herrington's (2007) view, "refocus the energy for learning on the student" who then becomes the "generator of knowledge". Comas-Quinn et al (2009) warn teachers that this type of activity may, in contrast, result in students feeling sceptical for having been requested to work in seemingly unfamiliar ways if they are not used to taking the lead in the classroom.…”
mentioning
confidence: 99%
“…Numerous researches have recommended FLIPPED CLASS MODE BASED ON THE PLATFORM OF WECHAT 361 MALL as a method of providing learners real-time collaborative learning experience. It has been shown that mobile phones are increasingly used for improving knowledge of vocabulary (Stockwell, 2010), grammar (Sung, Huang, & Chang, 2006), listening (Liu & Chu, 2010), and speaking (Rueckert, Kiser, & Cho, 2012), other than the four basic language skills, mobile phones can also be applied to other learning situations, such as foreign culture acquisition (Comas-Quinn & Mardomingo, 2009). …”
Section: How the Functions Of Wechat Cater To The Characteristics Of mentioning
confidence: 99%